RESPON AGAMATERHADAP KEKERASAN DALAM RUMAH TANGGA: Kajian tentang Nusyuz dan Hukumannya - Nurmahni, Nurmahni (Khatulistiwa, 2012)
Domestic violence becomes stagnant when faced with the culture of a society. Bad treatment of a wife by her husband because of disobedience or other reasons seems to be legitimized by religion and culture. A husband seems to have the right to treating his wife as he wishes. To understand domestic violence as a form of violence against women we need to look at it from women’s perspective. Without doing so, we will be trapped in myths leading us to a culture of victimizing women. The beating of a wife by a husband which is allowed in certain cases by religion should not be interpreted in a physical context but rather in a metaphoric-contextual perspective.